Selective Synthesis of Carbonates from Glycerol, CO2, and Alkyl Halides Using tert-Butyltetramethylguanidine - Mihara, Masatoshi; Moroga, Kaname; Iwasawa, Tetsuo; Nakai, Takeo; Ito, Takatoshi; Ohno, Toshinobu; Mizuno, Takumi (Synlett, 2018)
Herein, we describe the guanidine-promoted synthesis of carbonates from glycerol, CO2, and alkyl halides. Specifically, a linear tricarbonate (1,2,3-tri-O-butoxycarbonylglycerol), a dicarbonate [butyl (2-oxo-1,3-dioxolan-4-yl)methyl carbonate] containing a linear and a cyclic moiety, and a cyclic monocarbonate (4-hydroxymethyl-2-oxo-1,3-dioxolan) were selectively obtained in good yields, which were strongly affected by the steric bulkiness of the guanidine group substituents. The developed method exhibits the advantages of high efficiency and mild conditions, thus being a powerful tool for the synthesis of value-added products from industrial by-products.
Keywords: carbon dioxide; glycerol; carbonates; guanidines